M1/M2 Liver Macrophage Polarization After Antigenic Stimulation with Lipopolysaccharide (LPS) in Rats - Çaylan, Nida; Tektemur, Nalan Kaya; Colakoglu, Neriman; Dabak, Dürrin Özlem (My University, 2022)
Objective: In our study, we aimed to detect M1/M2 macrophage polarization in rat liver tissue by\rimmunohistochemical staining after antigenic stimulation with lipopolysaccharide (LPS).\rMaterials and Methods: Twenty-four Spraque-Dawley male 10-week-old rats were used in the\rstudy. Rats were randomly divided into 4 groups (n=6): Control-24 group, Control-48 group, LPS-\r24 group and LPS-48 group. Rats in the control groups were administered 1 mL of saline\rintraperitoneally (i.p) and the animals were decapitated after 24 or 48 hours. The rats in the LPS\rgroups were administered with 5 mg/kg LPS (in 1 mL saline) i.p. After 24 or 48 hours, the rats were\rdecapitated and the study was terminated.\rResults: Inflammatory cell infiltration and hyperemia were detected in liver tissues of rats in LPS-\r24 and LPS-48 groups as a result of examination of sections stained with hematoxylin-eosin (H&E).\rSinusoidal dilatation was also noted in the LPS-24 group. CD68 immunoreactivity was found to be\rsignificantly increased in LPS-treated rat liver sections when compared to control groups\r(P<0.001). CD68 immunoreactivity was significantly increased in the LPS-48 group compared to\rthe LPS-24 group (P<0.001). While no change was observed in the LPS-24 group in terms of\rCD163 and CD204 immunoreactivities compared to the control groups, CD163 and CD204\rimmunoreactivities were increased in the LPS-48 group compared to LPS-24, but this increase was\rnot statistically significant (P>0.05).\rConclusion: It was determined that the polarization of liver macrophages increased in the direction\rof M1 macrophages after antigenic stimulation with LPS in rats.
Keywords: Tıbbi Araştırmalar Deneysel; Biyokimya ve Moleküler Biyoloji; Hücre Biyolojisi; İmmünoloji; Veterinerlik